An Unusual Presentation of Lupus Vulgaris and the Practical Usefulness of Dermatoscopy - Grigorios Theodosiou; Marina Papageorgiou; Ioanna Mandekou-Lefaki (Case Reports in Dermatological Medicine)
We report a case report of lupus vulgaris (LV) presented on the extremities of an 80-year-old man. He was misdiagnosed as having psoriasis and referred to our department for a second-opinion evaluation. The discrepancy between the clinical manifestation which was misleading and the dermatoscopic findings raised the suspicion of an underlying granulomatous disease and we proceeded to skin biopsy. The histopathologic examination set the diagnosis of LV.